Extrusion control : machine-process-product - Harris, Holton E. (Munich, Germany : Hanser r Publishers, 2004)
'The author explains how quality in extrusion can be measured, controlled, and improved. In particular, he conveys an understanding of how extruders should be controlled and what good closed-loop controls can accomplish.'--BOOK JACKET.
Includes index.
Keywords: Plastics -- Extrusion